CUTANEOUS MYXOID CYST ON THE SCLEROTIC FINGER IN A PATIENT WITH DIFFUSE SYSTEMIC SCLEROSIS - Taeko Nakamura-Wakatsuki; Toshiyuki Yamamoto (Our Dermatology Online, 2013)
Skin tumors occurring on the scleroderma fingers are rarely seen. Swollen fingers are hallmarks of systemic sclerosis, and mucin deposition in the lesional skin is a constant feature in systemic sclerosis. Here we describe a case of cutaneous myxoid cyst on the flexor aspect of the sclerotic fingers in a patient with severe diffuse cutaneous systemic sclerosis. Cutaneous myxoid cyst is a relatively common benign tumor; however, cases of cutaneous myxoid cysts developing on the scleroderma fingers have not been reported to date. Mucin deposition in the sclerotic skin may be a predisposing factor in the induction of myxoid cyst on the scleroderma finger in our patient.